Hubungan antara Harga Diri, Kontrol Diri, dan Konformitas Remaja terhadap Perilaku Seksual Pranikah - Daratista, Indah; Chandra, Evi Kartika (Bulletin of Counseling and Psychotherapy, 2020)
In Metro City, especially in the northern metro sub-district, there are 5 high schools. Which consists of madrassas, private and public. Most of the students have already known the term dating (in a relationship with the opposite sex). Relationships established in adolescents, can trigger premarital sexual behavior. This study examines self-esteem, self-control, adolescent conformity and premarital sexual behavior. This research is interesting to discuss, because the results of this study are different from previous studies. Previous studies have a negative relationship between variables. But the results of this study indicate that the higher self-esteem, the higher the premarital sexual behavior. While the higher self-esteem of adolescents, the higher the self-control will be. When self-esteem and self-control go up, then adolescent conformity will also increase. The purpose of this study is to determine the relationships that arise between self-esteem, self-control, adolescent conformity and premarital sexual behavior. Which involved high school students in all sub-districts of the metro north of the city of metro, to be sampled in this study. The benefit of this research is to be able to increase the awareness of adolescents and the public about the dangers of premarital sexual behavior when performed. This study uses quantitative research with a correlation and survey approach. The results of this study are that there is a positive and significant relationship. Both the relationship between self-esteem with premarital sexual behavior, self-control with premarital sexual behavior, adolescent conformity with premarital sexual behavior, relationship between self-esteem with self-control, self-control with adolescent conformity, and self-esteem with adolescent conformity.